Synchronous double superficial mixed gastrointestinal mucus phenotype gastric cancer with gastritis cystica profunda and submucosal lipoma: A case report. Issue 22 (June 2018) - Huang, Dandan; Zhan, Qiang; Yang, Shudong; Sun, Qi; Zhou, Zhiyi
Abstract: Introduction: Synchronous double superficial gastric cancer with gastritis cystica profunda (GCP) and submucosal lipoma is a rare disease and is difficult to diagnose and treat. Case presentation: A 61-year-old man was referred to our hospital with upper abdominal discomfort for the past 10 days. One year ago, the patient underwent surgery for duodenal ulcer and perforation. The diseases were diagnosed by magnifying endoscopy with narrowband imaging and pathological methods. Both mucosal lesions with a submucosal yellow-colored nodule were completely resected by endoscopic submucosal dissection and additional proximal gastrectomy was performed on the cancer embolus in the submucosal vena cava. The patient was finally diagnosed with synchronous double superficial well differentiated adenocarcinoma (mixed gastrointestinal mucus phenotype) with embolus in submucosal vena cava, coexisting with gastritis cystica profunda and submucosal lipoma. Final TNM classification was T1b (sm1) N0M0, and pathological stage was IA. The postoperative course was uneventful, and no recurrence or metastasis was observed during the 5-month follow-up period. Conclusion: The diagnosis and treatment of synchronous double superficial gastric cancer with GCP and submucosal lipoma is challenging. In addition, elastic fiber staining and immune marker staining is effective and should be considered for diagnosis.